Classical integrable super sinh-Gordon equation with defects - Gomes, J. F.; Ymai, L. H.; Zimerman, A. H. (Iop Publishing Ltd, 2006)
The introduction of defects is discussed under the Lagrangian formalism and Backlund transformations for the N = 1 super sinh-Gordon model. Modified conserved momentum and energy are constructed for this case. Some explicit examples of different Backlund soliton solutions are discussed. The Lax formulation within the space split by the defect leads to the integrability of the model and henceforth to the existence of an infinite number of constants of motion.